The Effect of The Number of Msmes, The Number of Buildings and Grdp on City District Tax Revenue in South Sulawesi Province - Nur Alif Sapoetra; Abd. Rahim; Citra Ayni Kamaruddin; Sri Astuty; Abdul Rajab (International Journal of Economics and Management Sciences, 2026)
This research investigates the effect of the amount of MSMEs, the number of buildings, and GRDP on regional tax revenue in selected cities and regencies in South Sulawesi, driven by the inconsistency between the growth of economic potential and the realization of tax revenue, where increases in MSMEs, buildings, and GRDP are not always followed by higher tax receipts. The study aims to analyze the effect of these variables and identify the most significant factors contributing to regional fiscal capacity. A quantitative approach is employed using panel data that combine time series and cross-sectional data from 2015-2024, analyzed through panel data regression with model selection based on Chow, Hausman, and Lagrange Multiplier test. The results show that partially, MSMEs and the number of buildings do not have a significant effect on tax revenue, while GRDP has a positive significant impact; however, simultaneously, all variables significantly influence tax revenue, as indicated by a high Adjusted R-squared value. These findings suggest that economic growth, as proxied by GRDP, plays a more dominant role in increasing tax revenue compared to the mere increase in the number of MSMEs and buildings, implying that optimizing tax revenue requires not only expanding economic potential but also enhancing tax compliance, administrative efficiency, and the quality of economic growth.